PENERAPAN BALANCED SCORECARD SEBAGAI TOLAK UKUR DALAM PENGUKURAN KINERJA KARYAWAN PT. FEDERAL INTERNATIONAL FINANCE WAY JEPARA LAMPUNG TIMUR - Sugiono Sugiono (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
The balanced scorecard is a framework, a language that communicates vision, mission, and strategy to all employees about the key determinants of success now and in the future. In addition, the Balanced Scorecard also emphasizes that the measurement of financial and non-financial performance of this study uses descriptive techniques with a qualitative approach. The purpose of this study is to find out how the performance of PT. FIF reviewed the perspective of the balanced scorecard as a benchmark in measuring employee performance. In the financial aspect, the results were quite satisfactory, namely an increase of 3% - 5.7%, this was caused by the measurement technique using the balanced scorecard method which was quite reliable. Non-financial aspects, experience a good increase because in each foreign perspective and presence get positive results so that the profitability of up to 4% - 8.7%, it means that the performance of employees in the good category Performance measurement on the financial perspective on profitability ratios is considered quite good because ROE in December 2018 has decreased while ROI and Profit margins are considered stable.